Script concordance tests: A call for action in dental education. (24th January 2021) - Vital, Sibylle; Wulfman, Claudine; Girard, Félix; Tamimi, Faleh; Charlin, Bernard; Ducret, Maxime
Abstract: The Script Concordance Test (SCT) is an educational tool that aims to assess the ability to interpret medical information under conditions of uncertainty. It is widely used and validated in health education, but almost unknown in dentistry. Based on authentic clinical problem‐solving situations, it allows to assess clinical reasoning that experienced health workers develop over the years. A specific scoring system, dedicated to SCT, considers the variability of responses of practitioners in the same clinical situations. Finally, the scores generated by SCT reflect the respondents' ability to interpret clinical data compared to experienced clinicians. This article aims to familiarise the dental educators' community with SCT construction, optimisation and its possible applications.